Maritime security cooperation within the ASEAN institutional framework: a gradual shift towards practical cooperation - I Gusti Bagus Dharma Agastia (Centre for Business and Diplomatic Studies (CBDS) Bina Nusantara University, 2021)
How does ASEAN fare in addressing maritime security problems? This paper examines the shifting character of maritime security cooperation in Southeast Asia. In doing so, this paper looks at the outcomes of three maritime security-oriented fora that exist within the ASEAN regional framework: the ASEAN Regional Forum, the ASEAN Defence Ministers’ Meeting, and the ASEAN Maritime Forum. By compiling and analysing data on the forms and frequency of existing cooperative activities from 2003 gathered from publicly available sources, this paper finds that maritime security cooperation among ASEAN members continue to be largely dialogue-based, with few instances of practical cooperation. By comparing the three fora, this paper argues that the organisational design of these forums tends to affect the forms of cooperation. This paper concludes that despite ASEAN showing progress in adopting practical security cooperation, there remain hurdles in achieving regional maritime security.